The political instrumentalization of ethnic divisions and affiliations in Afghanistan (2001–2021) - Mirdad, Mohammad Ayub; Suyanto, Bagong; Hayat, Muhammad Umer (Masyarakat, Kebudayaan dan Politik, 2025)
The political instrumentalization of ethnicity is not a new issue and dates back to the time when the country’s name changed from Khorasan to Afghanistan. The ethnic divisions deepened during the presidencies of Hamid Karzai and Ashraf Ghani Ahmadzai. This article delves into the intricate dynamics of ethnic divisions and their political instrumentalization in Afghanistan from 2001 to 2021. While a lot of research has examined Afghanistan’s ethnic landscape, limited attention has been paid to how post-2001 leaders mobilized ethnic identities to entrench political power. Focusing on Hamid Karzai and Ashraf Ghani’s administrations, both from the Pashtun ethnic group, this study draws on Weale and Diamond’s theories of ethnic favoritism, dominance, and undemocratic leadership. Using a qualitative approach through document analysis and literature review, this study found that both leaders leveraged their ethnic identity to consolidate power and influence policymaking. Pashtuns were systematically favored in key governmental appointments, often at the expense of other major ethnic groups such as Tajiks, Hazaras, and Uzbeks. This political exclusion has deepened interethnic mistrust and fragmented the national fabric. By highlighting the long-term consequences of ethnic favoritism, this study contributes to ongoing debates on identity politics and governance in post-conflict states.